Advancement of power generation system by instalment of solar photovoltaic system for multiple wells: A Case Study. Issue 1 (1st March 2022) - Singh, Pushpendra; Sharma, Kedar; Talwariya, Akash
Abstract: This paper proposes the solution for electricity issues in agriculture sector of particular location in Rajasthan. The issues reported about the availability of ground water and availability of Electricity from electric Grid. The study proposes a centralized solar photovoltaic system for available nearby open wells, which are being operated by diesel engine pump-sets, which emits greenhouse gases and pollute the environment. The proposed centralized photovoltaic system will provide power for submersible pump sets. The additional available power can be stored in batteries, utilized for charging the batteries of electrical vehicles or sell back to electric grid. This paper shows the cost analysis for proposed systems that can be applied and effective centralized solar photovoltaic system in the area considered for study. Centralized solar photovoltaic generation supply to different consumers in different slots and may increase the conflict between consumers, demand side management provide suitable solution to consumers is proposed and analyse in future work.